Adolescent motivations to abstain from sex and alcohol: a self-determination theory approach. Issue 4 (2nd October 2022) - Hardy, Sam A.; Hurst, Jeffrey L.
Abstract: The purpose of this study was to design and validate a measure of adolescent motivations to abstain from sex and alcohol, grounded in self-determination theory, and to examine the roles of controlled and autonomous abstinence motivations in predicting these two risk behaviors. The sample included 799 U.S. adolescents, 15-18 years old. The abstinence motivation measure included 10 items, with five items each for controlled and autonomous abstinence motivations. The measure demonstrated strong psychometrics properties and validity. Controlled and autonomous motivations to abstain from sex and alcohol both correlated negatively with sex and alcohol behaviors. However, in structural equation models only autonomous abstinence motivation for a specific behavior predicted that behavior. A mediation model also found that autonomous but not controlled abstinence motivations mediated relations between religious involvement and risk behaviors. This study generated a theoretical-based measure of adolescent abstinence motivation. Additionally, autonomous abstinence motivations more strongly and uniquely predicted sex and alcohol behaviors than controlled abstinence motivations.